Complete chloroplast genome sequence data of Cannabis sativa - Jiao Xu; Lingyang Kong; Wei Wu; Chenliang Li; Weichao Ren; Wei Ma (Data in Brief)
Cannabis sativa, which is an annual erect herb belonging to the Cannabis family, possesses significant medicinal value. The entire genome of the cannabis chloroplast was sequenced using the Illumina NovaSeq 6000 on the Illumina high-throughput sequencing platform. The circular genome has a size of 153,871 base pairs (bp), consisting of two inverted repeats (IRs) that are 26,010 bp each, a large single copy region (LSC) measuring 84,038 bp, and a small single copy region (SSC) of 17,813 bp. A sum of 86 genes were identified and annotated. Among them, there were 48 protein-coding genes (PCGs), 30 tRNA genes, and 8 rRNA genes. Relying on the entire chloroplast genome and the PCGs sequence, a phylogenetic tree of six cannabis plants was established, with Arabidopsis serving as the outgroup.The phylogenetic results showed that Humulus scandens of Cannabaceae was closely related to the hemp in this study. These data enriched the genetic knowledge of Cannabidae plants and provided a basis for further research on molecular breeding and genetic breeding of Cannabidae.